Uncovering the ideology of familialism on families with special needs child : from a mother’s perspective - Leow, Renee Yi Ting (2018)
With the entrance of a special needs child into the family, it is a life long process for the family to manage every aspect of their well being, especially when the child is totally dependent. By living in a non-welfare state, the family is relied upon in the providence and management of caregiving, where each family has different experiences and strategies based on their socioeconomic position. Looking through the lens of the mothers, this study seeks to uncover the gendered roles of caregiving, ambivalence faced and the social actions enacted by mothers, their perspective of familialism and experiences with state and coping mechanisms. In-depth interviews were conducted with 14 mothers across different socioeconomic status to provide a comparison of their lived realities. Findings uncovered power relations and socioeconomic position that influence a mother’s structural strain, their construction of familialism and the administration of state and institutions on families.